The regulation of Oct4 in human gingival fibroblasts stimulated by cyclosporine A: Preliminary observations - Cheng-Chia Yu; Chia-Ming Liu; Tai-Chen Lin; Ni-Yu Su; Li-Chiu Yang; Yu-Chao Chang (Elsevier, 2020)
Background/purpose: Oct4, a key transcription factor, could reprogram human somatic fibroblasts into embryonic stem cell-like pluripotent cells. The exact mechanism of cyclosporine A (CsA)-induced gingival overgrowth is still unclear. The aim of this study was to investigate the effects of CsA on the expression of Oct4 in cultured human gingival fibroblasts (HGFs) in vitro. Materials and methods: The effects of CsA on HGFs were used to elucidate whether Oct4 expression could be induced by CsA by using quantitative real-time reverse transcription-polymerase chain reaction and western blot. Cell growth in CsA-treated HGFs with Oct4 lentiviral-mediated shRNAi knockdown was evaluated by tetrazolium bromide reduction assay. Results: CsA was found to upregulate Oct4 transcript in a dose-dependent manner (p < 0.05). CsA also dose-dependently increased Oct4 protein expression (p < 0.05). The lentivirus expressing sh-Oct4 successfully prevented the CsA-induced Oct4 mRNA and protein in HGFs (p < 0.05). However, knockdown of Oct4 was insufficient to inhibit CsA-stimulated cell growth in HGFs. Furthermore, double knockdown with pluripotency-associated transcription factor Nanog showed that the down-regulation of Oct4/Nanog by lentiviral infection significantly inhibited CsA-stimulated cell growth (p < 0.05). Conclusion: Taken together, CsA was first found to upregulate Oct4 mRNA and protein expression in HGFs. The silencing Oct4 could not suppress cell growth unless Nanog was repressed simultaneously.